The Large and Diverse Family of Mediterranean Flat Breads: A Database - Antonella Pasqualone; Francesca Vurro; Carmine Summo; Mokhtar H. Abd-El-Khalek; Haneen H. Al-Dmoor; Tomislava Grgic; Maria Ruiz; Christopher Magro; Christodoulos Deligeorgakis; Cynthia Helou; Patricia Le-Bail (Foods, 2022)
An in-depth survey was conducted by collecting information from web sources, supplemented by interviews with experts and/or bakers, to identify all the flat breads (FBs) produced in the nine Mediterranean countries involved in the FlatBreadMine Project (Croatia, Egypt, France, Greece, Italy, Jordan, Lebanon, Malta and Spain), and to have an insight into their technical and cultural features. A database with information on 143 FB types (51 single-layered, 15 double-layered, 66 garnished, 11 fried) was established. Flours were from soft wheat (67.4%), durum wheat (13.7%), corn (8.6%), rye, sorghum, chickpea, and chestnut (together 5.2%). The raising agents were compressed yeast (55.8%), sourdough (16.7%), baking powder (9.0%), but 18.6% of FBs were unleavened. Sixteen old-style baking systems were recorded, classified into baking plates and vertical ovens (tannur and tabun). Artisanal FBs accounted for 82%, while the industrial ones for 7%. Quality schemes (national, European or global) applied to 91 FBs. Fifteen FBs were rare, prepared only for family consumption: changes in lifestyle and increasing urbanization may cause their disappearance. Actions are needed to prevent the reduction of biodiversity related to FBs. Information in the database will be useful for the selection of FBs suitable to promotional activities and technical or nutritional improvement.